AB0857 Standardized Optimization of Analgesics in Patients with Knee Osteoarthritis and Severe Pain – a Feasibility Study. (9th June 2015) - van Tunen, J.A.C.; van der Leeden, M.; Bos, W.; Cheung, J.; van der Esch, M.; Gerritsen, M.; Peter, W.F.; Roorda, L.D.; Tijhuis, G.J.; Voorneman, R.; Dekker, J.; Lems, W.F.
Abstract : Background: Prescription of analgesics is complex in patients with knee OA and severe pain. We developed a protocol for the standardized prescription of analgesics based on the World Health Organization analgesic ladder (1) and the Beating osteoARTritis (BART) strategy for stepped care in hip and knee OA (2). Objectives: The aim of this study was to evaluate the feasibility and outcome of the analgesic protocol. Methods: Forty-nine patients with knee OA and severe knee pain (NRS≥7; range 0-10) were included. Analgesics were prescribed following an incremental protocol (Figure 1 ) for a period of six weeks. Pain intensity was evaluated every two weeks. When there was insufficient pain reduction (NRS-pain>5), a consultation at the rheumatologist was planned to offer an analgesic of the next step. Analgesics of the next step were added to analgesics of the previous step(s). Analgesic use was recorded. Knee pain (NRS-pain) and activity limitations (WOMAC-PF) were measured. Data were collected at baseline and after six weeks. Subsequently, patients started with exercise therapy. Results: At baseline 84% of the patients used analgesics. Of all patients, 77% used acetaminophen, 36% used NSAIDs and 16% used weak opioids. At baseline, analgesics were used irregularly and at an suboptimal dose. Analgesic use after six weeks is described in Figure 1 . The maximal daily dosage was used in 93% of the patients that used acetaminophen, in 66% of the patients that used NSAIDs, and in 44% of the patients that used weak opioids. Combinations of analgesics were common. No serious adverse events occurred. In 39% of the patients NRS-pain was ≤5 after six weeks. Despite NRS-pain>5, a further step in the analgesic protocol was not accepted by the patient (n=14) or not prescribed by the rheumatologist (n=13), the latter mostly due to contra-indications or side effects. Statistically significant and clinically relevant mean improvements from baseline were 19% (p<0.001) for pain and 12% (p=0.002) for activity limitations after six weeks. Conclusions: After six weeks, patients used analgesics regularly and often at a preferential dose. Prescription of analgesics following an incremental protocol reduces pain and activity limitations in patients with knee OA and severe pain. References: World Health Organization. Cancer pain relief: with a guide to opioid availability. Available at: http://whqlibdoc.who.int/publications/9241544821.pdf (accessed 14 January 2014). Smink AJ, et al. Clin Rheumatol 2011;30:1623-9. Disclosure of Interest: None declared